Federalism and Gender Equality in Local Governance of Nepal - Silwal, Yam Bahadur; Budhathoki, Drona (Nepal Journal of Multidisciplinary Research, 2025)
Background: The adoption of the federal system through the 2015 Constitution of Nepal marked a pivotal shift in governance, decentralizing power to provincial and local levels. A key objective of this restructuring was to enhance inclusive governance, particularly through constitutional mandates (Article 38) and electoral quotas designed to boost women's political participation. While these provisions have led to a significant increase in the numerical representation of women in local government, achieving substantive and meaningful participation remains a critical challenge. Objective: This study aims to examine the status of women's representation in Nepal's 2022 local elections, using the 2017 elections as a baseline, to assess the impact of federalism on gender equality in local governance. Methods: The research employed an explanatory sequential mixed-methods design, grounded in pragmatist philosophy. It integrated quantitative data from the Election Commission of Nepal on the 2017 and 2022 local elections with a qualitative review of existing literature, policies, and scholarly analyses. The theoretical framework was guided by Feminist Theory, to analyze patriarchal power structures, and Decentralization Theory, to evaluate the devolution of power. Findings: The study confirms that legal quotas have successfully increased women's numerical representation, with women holding over 40% of local government positions in both election cycles. However, a severe disparity persists between numerical presence and substantive power. Women remain overwhelmingly concentrated in secondary, mandated roles (e.g., Deputy Mayors, Vice-Chairpersons, and ward members), with minimal representation in executive leadership. Only 25 women were elected as Mayors or Chairpersons in 2022 (out of 753 possible positions). Furthermore, intersectional analysis reveals significant disparities among women: while Dalit women constitute 47.4% of female ward members due to specific quotas, their representation in higher offices is minimal, and women from Madhesi and Muslim communities are consistently underrepresented. Conclusion: Federalism and its accompanying quota system have created essential institutional space for women's entry into local politics in Nepal. However, entrenched patriarchal norms, biased intra-party nomination processes, and a lack of institutional support continue to act as formidable barriers to substantive representation and leadership. The study concludes that achieving genuine gender equality requires moving beyond quotas to implement structural reforms, capacity-building initiatives, and a cultural shift to ensure women can exercise meaningful decision-making power across all levels of local governance. Implication: The findings imply that Nepal's federal system must move beyond numerical quotas and implement targeted capacity-building and institutional reforms to ensure women's meaningful participation in local governance. Furthermore, policymakers must adopt intersectional approaches to address the unique barriers faced by women from marginalized communities like Dalits, Madhesis, and Muslims.